HAM/TSP: association between white matter lesions on magnetic resonance imaging, clinical and cerebrospinal fluid findings - Marzia Puccioni-Sohler; Emerson Gasparetto; Mauro Jorge Cabral-Castro; Carla Slatter; Cecilia M. Vidal; Romeu Domingues Cortes; Bruce R. Rosen; Caterina Mainero (Arquivos de Neuro-Psiquiatria)
OBJECTIVE: To investigate the association between clinical data, white matter lesions and inflammatory cerebrospinal fluid (CSF) findings in HTLV-1 associated myelopathy/tropical spastic paraparesis (HAM/TSP). METHOD: We studied brain and cervical spinal cord on magnetic resonance imaging (MRI) and CSF examinations of 28 Brazilian HAM/TSP patients. RESULTS: The majority of patients had severe neurological incapacity with EDSS median of 6.5 (3-8). The brain MRI showed white matter lesions (75%) and atrophy (14%). The preferential brain location was periventricular. Cervical demyelination lesions occurred in 11% of the cases, and cervical atrophy in 3.5%. One patient had enhancement lesions on T1 cervical spinal cord MRI. Cases with spinal cord lesions had signs of acute CSF inflammation. The brain white matter lesions predominated in the patients with higher age. CONCLUSION: Our data suggest that an active inflammatory process is associated with the cervical spinal cord lesions in HAM/TSP. The brain abnormalities are not related to the clinical picture of HAM/TSP.